The Arabidopsis MIK2 receptor elicits immunity by sensing a conserved signature from phytocytokines and microbes - Shuguo Hou (Nature Portfolio, 2021)
Peptide signals generated during plant microbe interactions can trigger immune responses in plants. Here the authors show that SCOOP12, a member of a family of peptides present in Brassicaceae plants, and SCOOP12-like motifs in Fusarium fungi, can trigger immune responses following perception by the MIK2 receptor kinase.